Pengaruh Keputusan Pendanaan, Profitabilitas, Solvabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan: (Studi Empiris pada Perusahaan Manufaktur Sektor Industri yang Terdaftar di Bursa Efek Indonesia periode 2019-2023) - Resya Zahrani Yulian; Desy Anggraeni (Jurnal Mutiara Ilmu Akuntansi, 2025)
Firm value represents the value required by investors to make investment decisions, as reflected in the company's market price. It also represents the growth value for shareholders, which is mirrored in the company's stock market price. Firm value signifies the prosperity of shareholders; when the firm's value is high, shareholder prosperity is also high. The objective of this study is to determine the influence of financing decisions, profitability, solvency, and company size on firm value. The population consists of industrial sector companies listed on the Indonesia Stock Exchange (IDX) with financial statements for the 2019–2023 period. The sample was selected using purposive sampling based on specific criteria, resulting in 41 companies. This study utilizes multiple linear regression analysis, facilitated by the SPSS Version 22 program. The results of this study indicate that funding decisions as measured by the debt to equity ratio have a positive and significant effect on firm value, profitability as measured by return on assets has a positive and significant effect on firm value, solvency as measured by the debt to asset ratio has a negative and significant effect on firm value, and firm size as measured by firmsize has no effect on firm value.